Justice as a Fundamental Principle of Law: A Meta-Normative Context - ZVONKOV, Yevgen Ye. (Journal of Advanced Research in Law and Economics, 2019)
In the proposed article, the author at the theoretical level considers the question of the meta-normativity of the justice content as a fundamental principle of law. It is noted that justice is the highest degree of law, whose norms must be set in accordance with its standards, some of which have an ideal, teleological dimension, and therefore their full implementation in a changing social environment cannot be achieved. The moral and regulatory context of justice implies that it is realized in life not in connection with possible coercive measures for violation of its formally defined rules, but for the good will of a person who exercises it freely. As a result of the study, the author concludes that the legal normativity of justice is conditioned by the presence of numerous social contradictions, freedom of individual moral choice and other objective factors that require the establishment of clear and relative criteria for its implementation in public relations.